78.1k views
3 votes
Solve the equation 3(2x + 2) = 3x − 15.

User Heeen
by
3.8k points

2 Answers

5 votes

Answer:

x = -7

Explanation:

3(2x+2) = 3x - 15

First, we should simplify on the left side.

6x + 6 = 3x - 15 ; Now we subtract six from both sides.

-6 -6

6x = 3x - 21 ; next we just subtract 3x from both sides.

-3x -3x

3x = -21

Finally, we divide 3 from both sides to separate the three from the x.

x = -7

Hope this helps!! <3 :)

User Petrona
by
5.8k points
2 votes

Hi there! :)

Answer:

x = -7.

Explanation:

Starting with:

3(2x + 2) = 3x - 15

Begin by distributing '3' with the terms inside of the parenthesis:

3(2x) + 3(2) = 3x - 15

Simplify:

6x + 6 = 3x - 15

Isolate the variable by subtracting '3x' from both sides:

6x - 3x + 6 = 3x - 3x - 15

3x + 6 = -15

Subtract 6 from both sides:

3x + 6 - 6 = -15 - 6

3x = -21

Divide both sides by 3:

3x/3 = -21/3

x = -7.

User Herms
by
5.1k points